Multiscale Textile‐Based Haptic Interactions - Zane A. Zook; Barclay Jumet; Anas Yousaf; Daniel J. Preston; Marcia K. O’Malley (Advanced Intelligent Systems, 2024)
Wearable haptic devices transmit information via touch receptors in the skin, yet devices located on parts of the body with high densities of receptors, such as fingertips and hands, impede interactions. Other locations that are well‐suited for wearables, such as the wrists and arms, suffer from lower perceptual sensitivity. The emergence of textile‐based wearable devices introduces new techniques of fabrication that can be leveraged to address these constraints and enable new modes of haptic interactions. This article formalizes the concept of “multiscale” interaction, an untapped paradigm for haptic wearables, enabling enhanced delivery of information via textile‐based haptic modules. In this approach, users choose the depth and detail of their haptic experiences by varying their interaction mode. Flexible prototyping methods enable multiscale haptic bands that provide both body‐scale interactions (on the forearm) and hand‐scale interactions (on the fingers and palm). A series of experiments assess participants’ ability to identify pressure states and spatial locations delivered by these bands across these interaction scales. A final experiment demonstrates the encoding of three‐bit information into prototypical multiscale interactions, showcasing the paradigm's efficacy. This research lays the groundwork for versatile haptic communication and wearable design, offering users the ability to select interaction modes for receiving information.